2018
DOI: 10.1007/s00105-018-4229-z
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der Phototherapie in der Behandlung des chronischen Pruritus

Abstract: Phototherapy and photochemotherapy (PUVA) are important treatment modalities in inflammatory skin diseases such as psoriasis and atopic dermatitis as well as in cutaneous T‑cell lymphoma (e.g., mycosis fungoides/Sezary syndrome). Many of these skin diseases are accompanied by distracting pruritus. In addition, patients may suffer from intense pruritus in systemic diseases of the kidney and liver as well as of the endocrine and hematopoietic system. UV-light during phototherapy is capable of not only improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…This core problem in itch research could be addressed by more precise clinical outcome measurements such as the number of scratch lesions, 61 determination of the quantity of topicals used or by investigation of the photobiological effect of phototherapy on the peripheral neurophysiology of itch in skin biopsies of study patients. 14,59 In conclusion, phototherapy proved to be a rapid, effective, safe and inexpensive treatment modality to reduce itch and to improve itch-related QoL in four out of five patients suffering from different itchy conditions. These data support previous studies 20,21,33,35,44,59,62 which demonstrated the continued importance of phototherapy in the era of targeted therapies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This core problem in itch research could be addressed by more precise clinical outcome measurements such as the number of scratch lesions, 61 determination of the quantity of topicals used or by investigation of the photobiological effect of phototherapy on the peripheral neurophysiology of itch in skin biopsies of study patients. 14,59 In conclusion, phototherapy proved to be a rapid, effective, safe and inexpensive treatment modality to reduce itch and to improve itch-related QoL in four out of five patients suffering from different itchy conditions. These data support previous studies 20,21,33,35,44,59,62 which demonstrated the continued importance of phototherapy in the era of targeted therapies.…”
Section: Discussionmentioning
confidence: 85%
“…Ultraviolet (UV) UVB (280-320 nm, epidermal effects only) and UVA (320-400 nm, mainly dermal effects) have an antipruritic effect on a) pruriceptive nerve fibers, by a decreased secretion of their pruritogenic neuropeptides (such as substance P, nerve growth factor (NGF), calcitonin gene-related peptide or endothelin-1) and b) various cell types that are involved in the peripheral neurophysiology of itch such as keratinocytes, dermal dendritic cells, Langerhans cells, mast cells, T-lymphocytes amongst others, resulting in a decrease of pruritogens such as substance P, thymic stromal lymphopoietin, interleukin (IL)-4, -13 and -31. [11][12][13][14][15][16][17] The UV-based modalities include narrowband (NB)-UVB (311-313 nm), UVA (320-400 nm), UVA1 (340-400 nm) and psoralen plus UVA (PUVA). 18 As NB-UVB has been proven to be more effective, less carcinogenic and associated with less side effects in the treatment of psoriasis, 19 broadband (BB)-UVB (280-320 nm) is rarely used nowadays.…”
mentioning
confidence: 99%
“…NB-UVB is clinically effective and improves quality of life in children with moderateto-severe eczema [97]. The effect is maintained for six months after treatment.…”
Section: Ultraviolet Phototherapymentioning
confidence: 96%
“…Since the patient will stay for at least three weeks, (balneo)phototherapy is the treatment of choice in most cases. There is strong evidence for the efficacy of UV therapy in chronic pruritus [25]. This can be enhanced by balneotherapy, but it should be noted that saline additives may not be well tolerated because of scratching excoriations.…”
Section: Content and Value Of Dermatological Rehabilitation For Patients With Chronic Pruritusmentioning
confidence: 99%